2019
DOI: 10.1007/s00167-019-05584-2
|View full text |Cite|
|
Sign up to set email alerts
|

Similar results with kinematic and mechanical alignment applied in total knee arthroplasty

Abstract: Purpose This meta‐analysis compared the results of kinematic alignment (KA) and mechanical alignment (MA) applied in total knee arthroplasty (TKA). Methods Randomized controlled trials and cohort studies comparing functional, radiological, and perioperative results and complications in TKA with KA and MA were collected from databases and included in the analysis. Results Nine trials were included. KA showed a better performance in terms of the Western Ontario and McMaster Universities Osteoarthritis Index (WOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
7
32
1
Order By: Relevance
“…Some studies indicated that the KA technique achieved a greater range of motion (ROM) and a higher rate of postoperative satisfaction compared with MA in TKA [6,7]. However, several researches suggested similar results with these two alignment techniques [8]. Hence, we speculate that the KA or MA alignment technique may not be suitable for every case, which means surgeons should choose KA or MA individually.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some studies indicated that the KA technique achieved a greater range of motion (ROM) and a higher rate of postoperative satisfaction compared with MA in TKA [6,7]. However, several researches suggested similar results with these two alignment techniques [8]. Hence, we speculate that the KA or MA alignment technique may not be suitable for every case, which means surgeons should choose KA or MA individually.…”
Section: Introductionmentioning
confidence: 89%
“…The primary outcome was Knee Society Score (KSS) 2011 [10], including symptoms (0-25), satisfaction (0-40), expectation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and functional activities (0-100) at the 1-year followup. Secondary outcomes included the range of motion (ROM) and the HKA angle.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…However, in the analysis of functional outcome scores the same study was used twice from Dossett et al 19 , 57 For KSS and Knee Society Function Scores (KSFS) they extrapolated data from an incomplete study. 58 Luo et al 59 concluded KA achieved functional, radiological and peri-operative results similar to those of MA without an increase in the complication rates. This paper did have some significant flaws in that the forest plots were incorrect due to an error in how the outcomes scores (WOMAC, OKS and KSS) were interpreted, and the meta-analysis included studies with different techniques for TKR alignment including KA, rKA and AA.…”
Section: Meta-analysesmentioning
confidence: 93%
“…Some studies indicated that the KA technique achieved greater range of motion (ROM) and higher rate of postoperative satisfaction compared with MA in TKA [6,7]. However, several researches suggested similar results with these two alignment techniques [8]. Hence, we speculate that the KA or MA alignment technique may be not suitable for every case, which means surgeons should choose KA or MA individually.…”
Section: Introductionmentioning
confidence: 90%
“…The main outcome was Knee Society Score (KSS) 2011 [10], including symptom (0-25), satisfaction (0-40), expectation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and functional activities (0-100) at the 1-year followup. Secondary outcomes included the range of motion (ROM) and HKA angle.…”
Section: Surgical Techniquesmentioning
confidence: 99%